(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Una sentenza attesa: Dobbs v. Jackson Women’s Health Organization - 2. Motivazioni offensive e preoccupanti - 3. Una decisione all’insegna del principio democratico e della chiarezza normativa? - 4. Questioni spinose - 5. Dobbs, ovvero la morte del potere di judicial review della SCOTUS? Dobbs: the alarming implications of a political overturning of the right to abortion ABSTRACT: With Dobbs v. Jackson Women’s Health Organization the Supreme Court of United States overturned Roe v. Wade, upending almost 50 years of abortion rights in the United States. In commenting the case this article highlights the many problems arising from the decision: its bringing about new divisive legal issues; its possible outreach in terms of other fundamental liberties that could soon be cancelled; and especially the decline of the Supreme Court legitimacy that could call into question its very judicial review power.